2016
DOI: 10.1590/0103-8478cr20140361
|View full text |Cite
|
Sign up to set email alerts
|

Shoot segment and substrate composition in rooting of juvenile ipe-roxo mini-cuttings

Abstract: This study aimed to evaluate the rooting capability of apical and nodal mini-cuttings of ipe-roxo (Handroanthus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
7
0
4
Order By: Relevance
“…The increasing productivity and quality of the Eucalyptus forests in Brazil are due to their adaptability to the varied edaphoclimatic conditions, research on genetic breeding, advances in technologies and knowledge related to the vegetative propagation of this genus (FERRARI, GROSSI, WENDLING, 2004;SANTANA et al, 2013), for commercial production of plantlets with high genetic quality and plant health (PIMENTEL et al, 2016). The mini-cutting is a plant propagation technique most commonly used for producing eucalyptus seedlings (BENIN et al, 2013;BRONDANI et al, 2014;WENDLING, DUTRA, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing productivity and quality of the Eucalyptus forests in Brazil are due to their adaptability to the varied edaphoclimatic conditions, research on genetic breeding, advances in technologies and knowledge related to the vegetative propagation of this genus (FERRARI, GROSSI, WENDLING, 2004;SANTANA et al, 2013), for commercial production of plantlets with high genetic quality and plant health (PIMENTEL et al, 2016). The mini-cutting is a plant propagation technique most commonly used for producing eucalyptus seedlings (BENIN et al, 2013;BRONDANI et al, 2014;WENDLING, DUTRA, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As estacas da região mediana do caule apresentaram maior percentagem de enraizamento (66,6%), número (3,2) e comprimento (3,82 mm) de raízes não diferindo significativamente das demais (Tabela 1 e Figura 4). Pimentel et al (2016), em experimento com miniestacas de ipê-roxo extraídas de regiões apicais e nodais, também observaram comportamento de enraizamento similar entre miniestacas obtidas destas diferentes porções, indicando que ambas podem ser utilizadas para produção.…”
Section: Resultsunclassified
“…A sobrevivência de um percentual elevado de miniestacas neste experimento (90 -100%) é um resultado positivo, bem como o enraizamento de pelo menos 50% das miniestacas oriundas de qualquer região do caule, apical, mediana ou basal, sem que tenha sido utilizado qualquer fitormônio. Petry et al (2013) destacam a importância da investigação de formas de propagação de baixo custo, como a estaquia. Em seus ensaios, verificaram que 14 espécies nativas de diferentes famílias apresentaram enraizamento sem a adição de fitormônios.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The inadequate rooting of P. peroba in sand might pose a problem for clones producers of this species. Pimentel et al (2016) demonstrated that substrates with lower densities showed higher porosity and lower water retention capacity, which allowed greater rooting capacity of Handroanthus heptaphyllus mini-cuttings. Mendoza-Hernández et al (2014) stated that the rooting substrate should have an apparent density between 0.3 and 0.8 g cm -3 .…”
Section: Substrates and Iba In Rhizogenesis Of Paratecoma Perobamentioning
confidence: 99%